Development of Particulate Matter and Heavy Metal Emission Factors for Kerman Copper Industries - N Mansouri; J Nouri (Tehran University of Medical Sciences, 2004)
An emission factor is a tool that is used to estimate air pollutant emissions to the atmosphere. It relates the quantity of pollutants released from a source to some activities associated with those emissions. To determine the quantity of pollutant released from copper and its alloys smelting furnaces, 63 samples from emission gases were collected on cellulose ester membrane filters in three 8-hour-shifts within 24 hours during a week at three locations. Samples were weighed and analyzed to measure the heavy metal content by flame atomic absorption spectrometry. The emission factors for location 1, without control equipment, for total particulate matter (TPM), Cu, Zn, Pb, Cr, Ni, and Cd were 87.689, 2.076, 37.071, 0.917, 0.023, 0.074, and 0.021 g/Mg of products respectively. Emission factors for location 3, with dedusting unit as control equipment, were 8.139, 0.152, 3.921, 0.055, 0.003, 0.008, and 0.007 g/Mg for the above-mentioned parameters respectively. Finally those were 95.828, 2.228, 40.992, 0.972, 0.026, 0.082, and 0.028 g/Mg as a whole set respectively. Samples of location 2 were collected from inlet of dedusting unit and their results were used only for dedusting unit efficiency calculation.